The Holocene at Lac de Creno, Corsica, France: a key site for the whole island - REILLE, M; Gamisans, J; Andrieu-Ponel, V; De Beaulieu, J.-L. (New Phytologist, 1999)
Two Holocene lake sequences from Lac de Creno, Corsica were analysed on the basis of 119 pollen spectra and with the support of 13 14C-calibrated dates. The lower part of one of these sequences, corresponding to the late- glacial period, has been published previously. The first third of the Post-glacial is characterized by very particular forest dynamics, namely the absence of a role for deciduous Quercus and Corylus, the presence of mesophilous vegetation types dominated by Taxus, and the major forest role of Erica arborea at lower and mean altitude. At about 7440 cal BP, the occurrence of a major anthropogenic action brought about significant changes in the vegetation, notably an increase of deciduous Quercus and the expansion of Quercus ilex. Later, three major human-induced events are identified: the first, at about 2290 cal BP, is the cause of a short local expansion of Abies; the second, at about 1150 cal BP, is the degradation of deciduous forests to the benefit of Fagus; the third, at about 310 cal BP, corresponds to the disappearance of Fagus and its replacement by Pinus. Pollen data indicate that Q. ilex, Abies and Fagus are not indigenous in Corsica but spread there during the Postglacial ; this probably took place at about 6980 cal BP for Q. ilex.
Keywords: Corsica; glacial vegetation; Holocene; pollen spectra; vegetation history